Optimal MSF plant design - Mussati, Sergio Fabian (2001)
The aim of this paper is to present a rigorous model for Multi-Stage Flash Evaporation System (MSF). The MSF system is represented as a No Linear Programming (NLP) model. The model incorporates a high number of non-linear restrictions; so the achievement of the global optimum is difficult. Here, the study of an algorithm for the system optimisation is presented.